A Sociolinguistics Analysis Of Addressing System Used In Rowling's Harry Potter and The Prisoner Of Azkaban - Widowati, Mahar Tri (2005)
This research paper is about English Addressing System used in the novel. This research focuses on the address terms used by the characters in the novel. While the objectives of the research are to identify the variations of address term used and to identify the social factors of the use of addressing system. This research is qualitative research. To collect the data, the writer uses documentation method. The writer observes and reads the novel to find the words or phrases that shows the use of address term and take them as data. Then the writer classifies them into several categories, and analyzes them by using Dell Hyme's speaking theory. Based on the data analysis, the writer found six kinds of address terms used, they are: (1) addressing using name which consists of three kinds, namely, using First Name (FN), using Last Name (LN), and using Nickname (NN); (2) addressing using family relationship, (3) addressing using title which consist of two kinds, namely: using parliament term and using academic profession; (4) addressing using intimate relationship; (5) addressing using respectful term; and the last (6) addressing using mockery. There are some social factors involved in using those term, they are: setting, or social context of the interaction; the participants involved in the conversation; the end, as the aim or purpose of interaction; and the topic of conversation which influences the choice of addressing term.